2022
DOI: 10.1186/s13756-022-01052-8
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of preventing and containing outbreaks of multidrug-resistant organisms and Candida auris during the coronavirus disease 2019 pandemic: report of a carbapenem-resistant Acinetobacter baumannii outbreak and a systematic review of the literature

Abstract: Background Despite the adoption of strict infection prevention and control measures, many hospitals have reported outbreaks of multidrug-resistant organisms (MDRO) during the Coronavirus 2019 (COVID-19) pandemic. Following an outbreak of carbapenem-resistant Acinetobacter baumannii (CRAB) in our institution, we sought to systematically analyse characteristics of MDRO outbreaks in times of COVID-19, focussing on contributing factors and specific challenges in controlling these outbreaks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 48 publications
0
73
0
Order By: Relevance
“…Our study also found that 8.6% of hospital-acquired BSI was caused by non-albicans Candida spp . There is limited information of fungal infections, particularly of non-albicans Candida infections, as the cause of BSI in LMICs [ 44 – 47 ] The relatively high proportion of fungemia in our data, compared with 1.1% in Thailand [ 46 ], could be due the complex, immunocompromised patient populations, with common invasive procedures and high antibiotic use, all of which are risk factors of invasive candidiasis [ 31 , 48 ]. Available data worldwide suggest increasing incidence of fungemia caused by non-albicans Candida species [ 44 , 49 , 50 ] together with increasing resistance.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our study also found that 8.6% of hospital-acquired BSI was caused by non-albicans Candida spp . There is limited information of fungal infections, particularly of non-albicans Candida infections, as the cause of BSI in LMICs [ 44 – 47 ] The relatively high proportion of fungemia in our data, compared with 1.1% in Thailand [ 46 ], could be due the complex, immunocompromised patient populations, with common invasive procedures and high antibiotic use, all of which are risk factors of invasive candidiasis [ 31 , 48 ]. Available data worldwide suggest increasing incidence of fungemia caused by non-albicans Candida species [ 44 , 49 , 50 ] together with increasing resistance.…”
Section: Discussionmentioning
confidence: 96%
“…Nonetheless, studies from China [ 25 ], India [ 22 ], Italy [ 26 ], Taiwan [ 21 ], reported an increase in the proportion or incidence rates of AMR infections in COVID-19 patients. Multiple possible reasons for an increase include the high antibiotic use, predominance of severe COVID-19 patients in intensive care unit (ICU) with multiple predispositions towards AMR infections and protracted hospital stay, overcrowding of patients, and limited guideline adherence [ 27 – 31 ]. Therefore, appropriate antimicrobial prescribing, accurate diagnosis and appropriate infection prevention control are crucial for both COVID-19 and non-COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…auris . 10 , 23 , 27 , 28 , 29 This requires an increased awareness of the risk of C . auris in patients coming from regions with an endemic occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the latter, K. marina is a pathogen-emerging bacterium [79,80] which can contribute to the formation of biofilms in different stages of the food chain, increasing the chances that more pathogenic bacteria, such as Listeria monocytogenes, can survive the sanitation processes or carry out cross-contamination [81]. A. Bohemicus, which belongs to the genus Acinetobacter, is instead widely studied for its strong ability to generate multi-pharmacological resistance and the horizontal transmission of resistance-associated genes [82]. As reported by several authors, this bacterium can grow in the environment (soil and water), and its presence in the food chain can occur [83,84].…”
Section: Antibacterial Activitymentioning
confidence: 99%